Electron microscopy, X-Ray diffraction and Mossbauer studies of PbFe0.5Nb0.5O3, PbFe0.5Ta0.5O3 and BaFe0.5Nb0.5O3 ceramics sintered from mechanoactivated nanopowders. Issue 1 (27th May 2016) - Gusev, A. A.; Raevskaya, S. I.; Titov, V. V.; Isupov, V. P.; Avvakumov, E. G.; Raevski, I. P.; Chen, H.; Chou, C.-C.; Kubrin, S. P.; Titov, S. V.; Malitskaya, M. A.; Sarychev, D. A.; et al.
ABSTRACT: The effect of high-energy mechanical activation on magnetic phase transition temperature TM of PbFe0.5 Nb0.5 O3, PbFe0.5 Ta0.5 O3, and BaFe0.5 Nb0.5 O3 perovskites has been studied. Mossbauer studies have shown that TM values in all the perovskites studied can be changed substantially by mechanical activation and subsequent annealing. The increase of TM by 40-50 K, as compared to corresponding single crystals and ceramics sintered from the non-activated powders, was achieved in the mechanoactivated powders of both lead-containing and lead-free perovskites studied.